Analysis of Refrigeration Cycle Performance with an Ejector - Wani, J.R. (EDP Sciences, 2016)
A conventional refrigeration cycle uses expansion device between the condenser and the evaporator which has losses during the expansion process. A refrigeration cycle with ejector is a promising modification to improve the performance of conventional refrigeration cycle. The ejector is used to recover some of the available work so that the compressor suction pressure increases. To investigate the enhancement a model with R134a refrigerant was developed. To solve the set of equations and simulate the cycle performance a subroutine was written on engineering equation solver (EES) environment. At specific conditions, the refrigerant properties are obtained from EES. At the design conditions the ejector refrigeration cycle achieved 5.141 COP compared to 4.609 COP of the conventional refrigeration cycle. This means that ejector refrigeration cycle offers better COP with 10.35 improvement compared to conventional refrigeration cycle. Parametric analysis of ejector refrigeration cycle indicated that COP was influenced significantly by evaporator and condenser temperatures, entrainment ratio and diffuser efficiency. Â© 2016 The Authors, published by EDP Sciences.